A constitutive and drought-responsive mRNA undergoes long-distance transport in pear (Pyrus betulaefolia) phloem. (April 2020) - Hao, Li; Zhang, Yi; Wang, Shengnan; Zhang, Wenna; Wang, Shengyuan; Xu, Chaoran; Yu, Yunfei; Li, Tianzhong; Jiang, Feng; Li, Wei
Highlights: We identified a constitutive and drought-responsive PbDRM mRNA in pear ( Pyrus betulaefolia ). The relative abundance of PbDRM significantly increased in several different scion cultivars when grafted onto P. betulaefolia rootstock under drought conditions. Silencing of PbDRM increased the drought sensitivity of P. betulaefolia . PbDRM mRNA moved from rootstock to scion as a phloem-mobile signal under drought stress. Abstract: Pear is one of the most commercially important fruit trees worldwide and is widely cultivated in temperate zones. Drought stress can greatly limit pear fruit yield and quality. Pyrus betulaefolia Bunge, a drought-resistant pear rootstock that is commonly used in northern China, confers favourable characteristics to pear scions, allowing them to respond rapidly to drought stress via the transport of macromolecules such as phloem-mobile mRNAs. How drought-responsive mRNAs function as phloem-mobile signals remains unknown, however. Here, we used RNA sequencing (RNA-seq) combined with SNP analysis to identify mobile mRNAs in P. betulaefolia . We focused on mobile mRNAs that respond to drought stress and found that the abundance of a novel mRNA named PbDRM ( P. betulaefoliaDROUGHT-RESPONSIVE MOBILE GENE ) significantly increased in several different scion cultivars when they were grafted onto P. betulaefolia rootstock under drought conditions. In addition, downregulating PbDRM by virus-induced gene silencing (VIGS) increased the drought sensitivity of P. betulaefolia . CAPS RT-PCR analysis confirmed that PbDRM mRNA moves from rootstock to scion in micrografting systems. Therefore, PbDRM mRNA acts as a phloem-mobile signal in pear under drought stress.